Empowerment Strategies to Build Food Security at The Miftahussalam Islamic Boarding School in Penagan Village, Indonesia - Sopian Hadi; Tayfur Dereli; Sajjid Husain; David Winkler (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2025)
Food security is a strategic issue for the sustainability of Islamic Boarding Bchools Miftahussalam in Bangka Regency utilizes non-productive land that has not been optimized. Local asset-based empowerment is needed to build sustainable food independence. Analyzing the strategy of empowering student in building independent food security through the asset-based community development (ABCD) approach. The study used the Participatory Action Research/PAR method with the approach through the 5 stages; Discovery, Dream, Design, Define, Destiny. The results of the study looked at what kind of empowerment strategies includes practical training in horticulture cultivation and utilization of non-productive land. non-productive land utilization. Implementation succeeded in increasing the food security of pesantren, reduce external supply dependence, and create a “green pesantren” model as an integrated agricultural learning center. pesantren” model as an integrated agricultural learning center. This is effective in building independent food security based on local assets through mobilizing the active participation of student, land optimization, and institutional strengthening. This program not only meets short-term food needs, but also creates economic and environmental sustainability. Recommendations further research includes the development of a student agripreneurship model and long-term economic impact analysis agripreneurship model and long-term economic impact analysis.